2019
DOI: 10.3390/app9081657
|View full text |Cite
|
Sign up to set email alerts
|

Model and Data-Driven System Portfolio Selection Based on Value and Risk

Abstract: System portfolio selection is a kind of tradeoff analysis and decision-making on multiple systems as a whole to fulfill the overall performance on the perspective of System of Systems (SoS). To avoid the subjectivity of traditional expert experience-dependent models, a model and data-driven approach is proposed to make an advance on the system portfolio selection. Two criteria of value and risk are used to indicate the quality of system portfolios. A capability gap model is employed to determine the value of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Big-sized portfolios still represent fewer cases and may configure an opportunity to be explored by future papers, since it may represent the reality of many modern companies with big data-sets. In the case of big-sized portfolios, all papers use traditional MCDM approaches, except for Wei et al [104], that used correlation analysis as an objective method. In some articles, researchers have used software, solvers, or programming languages to implement MCDM methods in R&D PPS.…”
Section: 3%mentioning
confidence: 99%
See 2 more Smart Citations
“…Big-sized portfolios still represent fewer cases and may configure an opportunity to be explored by future papers, since it may represent the reality of many modern companies with big data-sets. In the case of big-sized portfolios, all papers use traditional MCDM approaches, except for Wei et al [104], that used correlation analysis as an objective method. In some articles, researchers have used software, solvers, or programming languages to implement MCDM methods in R&D PPS.…”
Section: 3%mentioning
confidence: 99%
“…Wei et al [104] Model and Data-Driven System Portfolio Selection 2019 Samanlioglu et al [94] An intelligent approach for the evaluation of innovation projects 2020 Aghdaie et al [116] Decision making on exigent issues in organizations: a case study on R&D projects 2020 Yalcin et al [80] Research and Development Project Selection via IF-DEMATEL and IF-TOPSIS…”
Section: Montajabiha Et Al [9]mentioning
confidence: 99%
See 1 more Smart Citation
“…London et al [23] investigated the Markowitz PS problem and implemented several estimators to determine the expected return of a portfolio. Kumar and Doja [24] and then Wei et al [25] showed that the feasibility of replacing expert subjectiveness with knowledge based on the given information.…”
Section: Introductionmentioning
confidence: 99%